Understanding Financial Crises: Causes, Consequences, and Policy Responses - Stijn Claessens; M. Ayhan Kose; Luc Laeven; Fabián Valencia (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
The global financial crisis of 2007-09 has led to an intensive research program analyzing a wide range of issues related to financial crises. This paper presents a summary of a forthcoming book, Financial Crises: Causes, Consequences, and Policy Responses, that includes 19 contributions examining these issues and distilling policy lessons. The book covers a wide range of crises, including banking, balance-of-payments, and sovereign debt crises. It reviews the typical patterns prior to crises, considers lessons on their antecedents, and analyzes their evolution and aftermath. It also provides valuable policy lessons on how to prevent, contain and manage financial crises.
Keywords: E32; F44; G01; E5; E6; H12; 330; global financial crisis; sudden stops; debt crises; banking crises; currency crises; defaults; restructuring; welfare cost; asset price busts; credit busts; prediction of crises; Finanzkrise; Wirtschaftspolitik; Welt